Handbook Use and Health Education in the Knowledge Tuberculosis Patients - Munjiati Munjiati; Herry Prasetyo; Esti Dwi Widayanti (Jurnal LINK, 2013)
TB disease is a very serious disease, but with proper treatment of TB can be cured. To support the succes of Tuberculosis treatment program depends on knowledge about the prevention and treatment of patients with tuberculosis. The purpose of this study was to determine differences in the use of health education booklets with the knowledge of tuberculosis patients.This study used a quasi experimental research design. The design used was a pre test and post –test with control group design, in which the design is to measure the difference between an intervention and control group. The intervention group were given of pocket book for improving knowledge about tuberculosis, whereas the control group where given the health education. The health education was trained by someone who is fostered by the TB clinic. A total of 20 patients participated in the study of tuberculosis. The results of this study suggest the use of a pocket book for people with tuberculosis has a good correlation on the level of knowledge about the treatment and prevention of tuberculosis, in which the correlation is 0,75 and the health education have a correlaation of 0.68. Meanwhile, patients with tuberculosis were given a paperback book can be used as a media of health promotion for people with tuberculosis in the community.